2022
DOI: 10.1177/10711007221081868
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Results of the Modified Glide Path Technique for Improved Syndesmotic Reduction During Ankle Fracture Fixation

Abstract: Background: Malreduction after syndesmotic stabilization occurs in as many as 52% of cases and has been shown to detrimentally affect clinical outcomes. We propose that the modified Glide Path technique reduces the occurrence of syndesmotic malreduction. Methods: This study is a prospective series comparing 16 patients reduced with the modified Glide Path technique with a retrospectively reviewed series of 25 patients reduced with a traditional technique using fluoroscopy and a clamp. The modified Glide Path t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
0
4
0
2
Order By: Relevance
“…Another reason for DTFJ malreduction could be the applied intraoperative reduction technique. Published techniques included manual (thumb) reduction, 8 , 20 the glide path technique, 12 or the clamp technique. 4 , 24 Up to now, there is no agreement on the most appropriate reduction technique.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason for DTFJ malreduction could be the applied intraoperative reduction technique. Published techniques included manual (thumb) reduction, 8 , 20 the glide path technique, 12 or the clamp technique. 4 , 24 Up to now, there is no agreement on the most appropriate reduction technique.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that malreduction must be dedicated before the final fixation [ 40 ]. In this context, a modified glide path technique for syndesmotic reduction in ankle fracture fixation appears to reduce the rate of malreduction [ 41 ]. The static fixation of the syndesmosis by SYS was indicated by the lack of relevant divergence of the fibular drill channel to the tibial channel, as could have been assumed.…”
Section: Discussionmentioning
confidence: 99%
“…При использовании методов статической фиксации наблюдали самую высокую частоту мальредукции сустава и поломки имплантата, повторных операций, а в группе динамической фиксации -самую высокую частоту неанатомичной фиксации синдесмоза. В группе комбинированных методов наблюдали самую низкую частоту осложнений, это связано с тем, что данная техника позволяет зафиксировать синдесмоз как в области передней тибиофибулярной связки, так и в области задней тибиофибулярной связки, снижает риск поломки имплантата, неанатомичного сращения, но повышает риск ятрогенного перелома [38][39][40][41].…”
Section: гений ортопедии 2024;30(1)unclassified